Peranan Kreativitas dan Inovasi dalam Meningkatkan Volume Penjualan Pada PT. Nippon Indosari Corpindo Tbk - Wiwin Winarsih; Putri Andriani (UNIVED Press, 2022)
Research aims to understand the role of creativity and innovation in increase the volume of sale and described all forms of and the process relating to an a product produced in bread with a “Sari Roti”.The writer be assigned PT. Nippon Indosari Corpindo Tbk as an object research since the volume of sales in the past year decreased.It is due to the covid-19, the decline in the volume of sale a matter currently faced by PT. Nippon Indosari Corpindo Tbk now. Data analysis using, qualitative descriptive in the form of exposure data from raw ingredients, production process until the marketing obtained from observations directly and supported by secondary data from various sources. Use of data using interviews and study. Literature to entice consumers, the varying, the design is interesting is expected to maintain the quality of the product on the market and has high selling values. The result of research conducted showed that creativity and innovation in an enterprise very important because very helpful increase the volume of sales in the company and are also sources of out of the necessity to business security .The application of creativity and innovation has produced new strategies to increase the volume of business sales. A kind of bread that was originally not too much variant think have now been as well as to various kinds of kinds of variant taste .The same thing happened to the strategy and the right policy very needed at in determining success or failure in increase the volume of sales .As the strategy marketing is a way to accomplish a purpose of a corporation , so that in the run the utmost effort there needs to be the development of through a strategy of marketing.